Bygden, järnet och klostergodset i Tvååker och Sibbarp - Mascher, Catharina; Connelid, Pär (Hikuin, 2004)
Landscape changes in early Medieval Halland: farming system, iron production and the expansion of a monastic estate in the parishes of Tvååker and Sibbarp By Catharina Mascher & Pär Connelid This article deals with the landscape and settlement history in the parishes of Tvååker and Sibbarp in central Halland, with focus on the dynamic period c. AD 900-1300. During the early Middle Ages, several dramatic changes in the agrarian society and landscape occurred in the investigated area. Among the most important landscape changes were the dissolution of prehistoric farming and land ownership systems together with a re-organisation of the settlement structure. Just like other parts of western and southern Sweden, the county of Halland is rich of traces from prehistoric farming. Most notable are the extensive cairn fields, which in many places date back to the late Neolithic Period, and the large coaxial field systems that were established during the late Iron Age. The prehistoric farming system, represented by the cairn fields, was characterised by a dynamic land use. Small plots of arable fields lay spread in a vast grasslands, mainly used for fodder production. Some fields were manured and intensively tilled, while others were managed with a fallow rhythm. From recent investigations, we know that the settlement in some cairn fields consisted of several households managing the land together. The cairn fields are mainly found in the highland regions, rich of woodland. Traces of prehistoric farming in the coastal zones and in the today heavily cultivated plain areas, are much more hard to detect. During the late Viking Age, new ways of regulating disposal rights to land were implemented on ground. Large systems with regularly divided strip fields were established on the best land, often in the former cairn fields (and their equivalents in the plain areas). This radically new and systematic dividing of land can be seen as an effect of important changes in the contemporary society. At this time, the Danish kingdom became more consolidated and powerful in many respects. The strict system with land divisions presumably meant better methods for an authority to control property, land use, taxes and the flow of agrarian products. The incitement to control land and property could be realised through a socio-political system with a powerful (royal) elite and their local representatives. Around 1200, the strip field-systems lost their initial function as new, more intensive, cropping patterns were introduced. These changes must be seen in the light of the new social, political and economic orders that emerged in the Medieval society. Several of the larger settlement units were dissolved and some farms either moved to new places on the former outlands or were abandoned. As the importance of animal production continuously grew during the Middle Ages, significant areas of arable were turned into grazing and meadow land. Also, the iron production that flourished in the area during the period c. 900-1200 AD, rapidly decreased in the early Medieval period. The iron work was located around the archaeologically documented water mill by the streamlet Sandabäcken, situated on the land belonging to the historical farms Ugglehult and Dövared. According to the investigations, an important amount of iron was factored here. Soil for the iron melting and wood for the charcoal needed to run the ovens, was most likely collected in the nearby area. It is assumed that the iron production was controlled by people based in the local agrarian society. One hypothesis is that some (powerful) farmers themselves ran the iron work along with their ordinary farming activities. For some reason, the iron production disappeared from the area c. 1250. At this stage, the foundation of a monastic estate had also entered the scene in Tvååker. In the year 1197, Absalon, the bishop of Lund, donated an episcopal estate (villa or grangie) in Tvååker to the cistercians at the abbey of Sorö on Zealand. Only five years later, 1202, a dispute concerning the extension of the monastic estate took place and the archbishop Sunesen personally had to confirm the boundary and define it’s outer landmarks. From the (sometimes vague) descriptions of important boundary localities in the document from this event, the estate can be roughly reconstructed. In the document, two of the sites mentioned are the “iron mill” and “south iron works”. According to our analysis of the document, and in view of the landscape history in the area, it seems likely that the iron mill at Sandabäcken was located just outside the monastic estate. It also seems to be the fact that the monks never were engaged in the iron production at this particular mill. As mentioned above, the iron production decreased c. 1250, shortly after the cistercians had established their estate in Tvååker. If there is an a priori connection between these two events, we still don’t know. Presumably, the expansion of the cistercians in the area, led to changes in both economical and judicial matters for the neighbouring farmers. The donation of land to the monastery at Sorö, probably meant that important resources were lost for the people involved in farming and producing iron. Further, it’s likely that the donation also meant changes in the social hierarchy of the area, which could have led to a withdrawal of people with the economic interests (both capital and manpower) that guaranteed the iron production. The article stresses the importance of analysing the three components discussed above – that is, changes in land management, the rise and fall of the iron production and the foundation of a monastic estate (grangie) in the Tvååker-Sibbarp area – in a broad historical-geographical context. Seen together, as parts of a big puzzle, these three components can throw new light on the complex early Medieval society in Halland and Denmark.